Growth and Physiological Attributes of Rice by the Inoculation of Osmotolerant Rhizobacteria (Enterobacter flavescens) under Drought Condition - Hasna Dyah Kusumardani; Triwibowo Yuwono; Diah Rachmawati (Journal of Tropical Biodiversity and Biotechnology, 2022)
Rice (Oryza sativa L.) has mechanism for morphological, physiological, and biochemical self-defense in response to drought conditions. The ability of osmotolerant rhizobacteria to develop association with plants suggests that it could be used as an inoculum to support plant growth under drought stress. The purpose of this study is to determine the response of ‘IR64’ and ‘Situ Bagendit’ to the inoculation with osmotolerant rhizobacteria under drought conditions. The experiment had 3 treatment factors: 2 rice cultivars ('IR64' and 'Situ Bagendit'), 3 drought treatments (25%, 50% and 100% field capacity), and 2 types of rhizobacteria treatments (without inoculation and with inoculation using osmotolerant rhizobacteria (Enterobacter flavescens). Plant growth was measured in terms of plant height, number of leaves, number of tillers and panicles, and percentage of filled grain. Physiological and biochemical parameters, namely chlorophyll, carotenoids, proline, superoxide dismutase (SOD) peroxidase (POX) and ascorbate peroxidase (APX) were measured. The inoculation of osmotolerant rhizobacteria enhanced ‘IR64’ and ‘Situ Bagendit’ growth (plant height, number of leaves, tillers and panicles) and increased the percentage of grains in ‘IR64’ cultivar. Proline content, SOD, and APX activities were all increased by osmotolerant rhizobacteria inoculation, however, carotenoid content was decreased. Plant growth, physiological and biochemical responses of both cultivar to drought were enhanced by inoculation with osmotolerant rhizobacteria.